Digging Into The Beauty Of Language: Effective Balaghah Learning Strategies In The Digital Age - Muhammad Afthon Ulin Nuha; Ubay; Nurul Musyafaah (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
This study discusses the impact of digital technology on Balaghah learning among students. Through the implementation of interactive media, educational videos, and gamification elements, the literature indicates potential improvements in students' understanding of Arabic language theories. Digital technology not only enhances engagement and motivation for learning but also provides broader access to information sources, allowing students to explore the material independently. Despite challenges such as student distraction, the advantages of integrating technology appear to outweigh the drawbacks. The study emphasizes the need for effective classroom management approaches to minimize disruptions. By applying innovations in learning, it is hoped that students will gain a deeper understanding of Balaghah theories and appreciate the beauty of the Arabic language. The literature highlights the importance of technology in creating engaging and relevant learning experiences for students in the digital age.